Model Simulasi untuk Memperkirakan Tingkat Penjualan Garam Menggunakan Metode Monte Carlo - Muhammad Thoriq; Aldo Eko Syaputra; Yofhanda Septi Eirlangga (SEULANGA SYSTEM PUBLISHER, 2022)
The increasing need for salt in the West Sumatra area is inversely proportional to the raw material for making salt. So the stock of salt for consumption becomes less. This causes the purchasing power to be cut off for the needs of regional consumers. Based on these problems, a research was conducted by conducting simulations to predict the amount of salt sales in controlling stock. This study aims to predict sales in maintaining service to consumer demand. The method that can be used in making predictions is the Monte Carlo Method by processing Salt sales data in 2019, 2020, and 2021 at PT. Prosperous Grace. The results of the study are able to predict sales of salt in the form of kilograms (kg) in the future. The average accuracy rate in 2020 is 88% and in 2021 is 91%. So that this research can be a reference in decision making by PT. Kurnia Sejahtera to improve services.